1990
DOI: 10.1039/an9901501271
|View full text |Cite
|
Sign up to set email alerts
|

Determination of diethanolamine and morpholine in systems containing copper(II) using liquid chromatography

Abstract: A method is described for determining 2,2'-i m i no bisetha no1 (diet ha nola m i ne) and tetra hyd ro-I ,4-isoxazi n (morpholine) in a system containing copper(1l). By using a more powerful complex-forming agent, copper(l1) is removed from the sample, and the compounds to be determined are extracted with acid and separated on a strongly acidic sulphonated cation-exchange column with phosphate buffer as the mobile phase. The relative error of the method is less than 5%, the detection limit being 20 p.p.m. for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The analytical results obtained by the proposed method were compared with those obtained using the methods reported in the literature 9,10,13,14 for determining DEA. The results are summarized briey in Table 1 and indicated that this method provided similar recovery and RSD.…”
Section: Comparison Of the Proposed Methods With Other Methods Used I...mentioning
confidence: 99%
See 2 more Smart Citations
“…The analytical results obtained by the proposed method were compared with those obtained using the methods reported in the literature 9,10,13,14 for determining DEA. The results are summarized briey in Table 1 and indicated that this method provided similar recovery and RSD.…”
Section: Comparison Of the Proposed Methods With Other Methods Used I...mentioning
confidence: 99%
“…5 Therefore, an efficient, reliable and sensitive analytical method is indispensable for the detection of DEA. Some techniques, such as gas chromatography (GC), [6][7][8][9][10] high performance liquid chromatography (HPLC), [11][12][13][14] titration, 15 ion chromatography (IC), 16,17 capillary electrophoresis (CE), 18 eld asymmetric ion mobility spectrometry (FAIMS) 19 and spectrophotometry, have already been reported for the determination of DEA or alcamines. 20 Of these methods, titration is the stated standard method used in the chemical industry standard of China for determination of DEA in industrial use (HG/T 2916-1997).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation